Physics of Spin in Solids: Materials, Methods and Applications - Halilov, Samed (NATO Science Series II: Mathematics, Physics and Chemistry, Mathematics, Physics and Chemistry ;, 2005)
Most recent publications on spin-related phenomena focus on technological aspects of spin-dependent transport, with emphasis on the specific needs of spintronics. The present publication targets rather fundamental problems related to the physics of spin in solids, such as: (1) manifestation of spin and orbital polarization in spectroscopy, including valence and X-ray photoemission, magneto-optics, low-energy electron scattering on the surface; (2) application of new methods for interpretation and determination of magnetic low-lying excitations in the bulk and on the surface; (3) recent progress in evaluation of different type of magnetic forces including spin-orbit and exchange interaction, with subsequent determination of anisotropy and spin-ordering structure; (4) general problems of spin-dependent transport in semiconductors and metals, such as current-caused torque effect on spins at interfaces and spin injection in quantum dot systems; (5) problems in understanding the spin-dependent trends in unconventional superconductors; (6) many-body problems in solid state physics and recent progress in evaluation of self-energy effects; (7) fabrication of new magnetic materials with pre-programmed properties based on assembly from nano-particles, etc.